2015
DOI: 10.18632/oncotarget.5834
|View full text |Cite
|
Sign up to set email alerts
|

The HMG-CoA reductase inhibitor, simvastatin, exhibits anti-metastatic and anti-tumorigenic effects in ovarian cancer

Abstract: Ovarian cancer is the 5th leading cause of cancer death among women in the United States. The mevalonate pathway is thought to be a potential oncogenic pathway in the pathogenesis of ovarian cancer. Simvastatin, a 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR) inhibitor, is a widely used drug for inhibiting the synthesis of cholesterol and may also have anti-tumorigenic activity. Our goal was to evaluate the effects of simvastatin on ovarian cancer cell lines, primary cultures of ovarian cancer cells and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 53 publications
3
64
0
Order By: Relevance
“…It has recently been reported that obesity and subsequent hyperlipidemia are critical prognostic factors in EOC (35,36), and that statins, which are antihyperlipidemic agents, are expected to improve EOC prognosis (37). Interestingly, hLSR, which we identified as a new target in EOC, is related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 82%
“…It has recently been reported that obesity and subsequent hyperlipidemia are critical prognostic factors in EOC (35,36), and that statins, which are antihyperlipidemic agents, are expected to improve EOC prognosis (37). Interestingly, hLSR, which we identified as a new target in EOC, is related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 82%
“…HMGCR is the rate-limiting enzyme in de novo synthesis of cholesterol in vivo. Recent studies have reported that HMGCR is upregulated in several types of cancer including gastric [34], ovarian [7] and breast cancers [35], suggesting that HMGCR plays an oncogenic role. SREBF2 is a membrane-bound transcription factor that regulates cholesterol homeostasis in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have demonstrated that cholesterol accumulate in a series of human cancers, including breast [2], colon [3], prostate [4], HCC [5], and others [6]. In addition, enzymes involved in cholesterol metabolism have been reported abnormal expression in cancer tissues [7, 8]. For instance, cholesterol acyltransferase (ACAT)2, is found to be induced and promotes esterification of excess oxysterols for secretion to avoid cytotoxicity in a subset of hepatocellular carcinomas (HCCs) for tumor growth [9], suggestive of a specific cholesterol metabolic pathway in HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, preclinical studies have found that statins also have antineoplastic potential through the induction of tumor cell apoptosis and inhibition of tumor cell proliferation, invasion, and migration [810]. These effects have also been shown in ovarian and endometrial cancer-derived cell lines [1112]. Indeed, a body of epidemiologic studies has demonstrated that statins are associated with improved survival outcomes in several malignancies, including breast, gastric, colorectal, prostate, and kidney cancer [1317].…”
Section: Introductionmentioning
confidence: 99%